MEDIA PERMAINAN KARTU HURUF DALAM PEMBELAJARAN BAHASA PADA PENDIDIKAN DI TK HANDAYANI BUAY BAHUGA TAHUN AJARAN 2024/2025 - Intan Asykurina Billa; Ahmad Rifai’l Abun; Tamyiz (UNISAN JURNAL, 2025)
This study aims to provide an in-depth analysis of the implementation of letter card game media in language learning at TK Handayani Buay Bahuga in the 2024/2025 academic year and to identify supporting and inhibiting factors in its application. The letter card game is one of the innovative learning media designed to optimize early literacy skills in young children, including letter recognition, phonetic awareness, vocabulary development, and early reading abilities. This research employs a qualitative approach with a case study design, focusing on real learning situations in the classroom context. Data were collected through direct classroom observations, in-depth interviews with classroom teachers and the principal, as well as documentation of learning activities and students’ work. The findings reveal that the use of letter cards successfully creates an engaging, interactive, and enjoyable learning atmosphere conducive to children's language development. Children showed greater enthusiasm, confidence in communicating, and improved mastery of letters and sounds. Beyond language skills, the media also promoted fine motor development, concentration, and active participation. Supporting factors include teacher creativity, administrative support, adequate classroom facilities, and children’s intrinsic motivation. Inhibiting factors involve limited instructional time, variation in children's ability levels, and challenges with children who have short attention spans. Overall, letter card game media proved effective in enhancing early literacy and language acquisition in young learners.